2022
DOI: 10.2174/1871526522666220620115006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis in Prisoners: A Systematic Review of Current Evidence

Abstract: Introduction: Prisoners represent high-risk behaviors such as injecting drug use, sharing syringes, tattooing, and unprotected sexual intercourse. The authors aimed to study the prevalence of hepatitis B, hepatitis C, and hepatitis D in the prisoners. Methods: We conducted a systematic search using the keywords in online databases of PubMed, Web of Science, Scopus, and Science Direct. Two independent researchers examined the quality of the articles and the probable risk of bias. The most relevant articles b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…In one study conducted in Taiwan, 62.8% (570/908) of inmates were IV drug abusers, and among them HIV had a high prevalence of 21.6% 57 . In one systematic review of 23 articles, shared contaminated needles for IV drug use was reported as one of the principal hepatitis transmission routes among prisoners 59 . In another study carried out in Nigeria, 29.6% of inmates who used injection drugs were HCV positive 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study conducted in Taiwan, 62.8% (570/908) of inmates were IV drug abusers, and among them HIV had a high prevalence of 21.6% 57 . In one systematic review of 23 articles, shared contaminated needles for IV drug use was reported as one of the principal hepatitis transmission routes among prisoners 59 . In another study carried out in Nigeria, 29.6% of inmates who used injection drugs were HCV positive 39 .…”
Section: Discussionmentioning
confidence: 99%
“…57 In one systematic review of 23 articles, shared contaminated needles for IV drug use was reported as one of the principal hepatitis transmission routes among prisoners. 59 In another study carried out in Nigeria, 29.6% of inmates who used injection drugs were HCV positive. 39 Similarly, one large study among 1336 inmates in Ghana, indicated intravenous drug use, history of sharing syringes and drug paraphernalia, as independent determinants for HIV, HBV, and syphilis.…”
Section: Alcohol and Drug Usementioning
confidence: 97%
“…Our data, therefore, support the adoption of double reflex testing policies at a national level. If this is not possible, high-risk groups such as prisoners could be prioritized[ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%